The effect of introducing a Trauma Network on patient flow, hospital finances and trainee operating. Issue 2 (February 2015) - Hipps, Daniel; Jameson, Simon; Murty, An; Gregory, Rob; Large, David; Gregson, Jackie; Refaie, Ramsay; Reed, Mike
Abstract: In April 2012 the National Health Service in England introduced the Trauma Network system with the aim of improving the quality of trauma care. In this study we wished to determine how the introduction of the Trauma network has affected patient flow, hospital finances and orthopaedic trauma training across our region. The overall pattern of trauma distribution was not greatly affected, reflecting the relative rarity of major trauma in the UK. A small decrease in the total number of operations performed by trainees was noted in our region. Trainees at units designated as Major Trauma Centres gained slightly more operative experience in trauma procedures overall, and specifically in those associated with high energy, such as long bone nail insertion and external fixation procedures. However, there have been no significant changes in this pattern since the introduction of the Trauma Networks. Falling operative numbers presents a challenge for delivering high quality training within a surgical training programme, and each case should be seen as a vital educational opportunity. Best practice tariff targets for trauma were delivered for 99% of cases at our MTCs. Future audit and review to analyse the evolving role of the MTCs is desirable.